Efeitos de diferentes sistemas de cultivo in vitro sobre o crescimento de folículos pré-antrais isolados de ovários de fetos bovinos - Basso, Andréa Cristina; Garcia, Joaquim Mansano [UNESP]; Esper, Cesar Roberto [UNESP] (My University, 2007)
The objective of this study is to use different in vitro culture systems of preantral follicles from Nelore breed bovine fetuses in the last gestation quarter. The evaluation of treatments considered the time of growth of isolated follicles. Preantral follicles were mechanically isolated and submitted to the individual culture, for 9 days, in media no supplemented or supplemented with fetal calf serum (FCS), bovine serum albumin (BSA) or synthetic defined supplement substitute of serum KnockoutSR (KNO). We have also evaluated the effects of collagen gel or fetal calf fibroblast monolayer as substratum for in vitro cultures. The increase on the follicular diameter was followed in the first day (0 h), at the 72 h, 144 h and 216 h. Considering cultures of isolated follicles, the results have shown that the association between media supplemented with FCS and collagen gel was significantly more efficient on the increase of the follicular diameter than other treatments. It is not still established a system of appropriate cultivation that sustains the differentiation and multiplication of the granular cells and that maintains the contact of the same ones with the oocyte to provide molecules and factors that supply the metabolic demand. We also understand that our results also represent another promising step on the search for the ultimate system of in vitro culture of preantral follicles from bovines.
Effects of different systems of in vitro culture on the isolated preantral follicles from fetal bovine ovaries
Keywords: Bovine; Calf; Follicle; In vitro culture; Preantral; Bovinae